Vigorexia: entre o vício, a saúde e o estilo de vida - Lopes, Mirela Valério (2014)
Current article aims discussing Brazilian people body esthetic standards especially male, who recently had it discovered‟ by the media and esthetic product companies, imposing over it a new standard to be achieved. Media pressure would be the main responsible of imposing those new standards, of said so perfect body‟, the ones who takes individuals to over exceed as using steroids to speed muscles building up and also over exercising repetitively even when not necessary, so called vigorexia‟ - a disturb caused by exercising and also an image disturb in which exercisers cannot realize their bodies being build